Tháng Sáu 18, 2024

Với \(x < 2\) thì biểu thức \(\sqrt {{{\left( {2 – x} \right)}^2}} + x – 3\) có giá trị bằng A \( – 1\) B \(2x – 5\) C \(5 – 2x\) D \(1\)

Với \(x < 2\) thì biểu thức \(\sqrt {{{\left( {2 – x} \right)}^2}} + x – 3\) có giá trị bằng

A \( – 1\)

B \(2x – 5\)

C \(5 – 2x\)

D \(1\)

Hướng dẫn Chọn đáp án là: A

Phương pháp giải:

Biểu thức \(\sqrt {f\left( x \right)} \) xác định \( \Leftrightarrow f\left( x \right) \ge 0.\)

Sử dụng công thức \(\sqrt {{f^2}\left( x \right)} = \left| {f\left( x \right)} \right| = \left\{ \begin{array}{l}f\left( x \right)\,\,\,\,khi\,\,\,\,f\left( x \right) \ge 0\\ – f\left( x \right)\,\,\,\,khi\,\,\,f\left( x \right) < 0\end{array} \right..\)

Lời giải chi tiết:

Điều kiện: \({\left( {2 – x} \right)^2} \ge 0 \Leftrightarrow x – 2 \ne 0 \Leftrightarrow x \ne 2.\)

\(\begin{array}{l} \Rightarrow \sqrt {{{\left( {2 – x} \right)}^2}} + x – 3 = \left| {2 – x} \right| + x – 3\\ = 2 – x + x – 3\,\,\,\,\,\left( {do\,\,\,\,\,x < 2 \Rightarrow 2 – x > 0} \right)\\ = – 1.\end{array}\)

Chọn A.